Leaf Morphology, Photosynthetic Performance, Chlorophyll Fluorescence, Stomatal Development of Lettuce (Lactuca sativa L.) Exposed to Different Ratios of Red Light to Blue Light - Wang, Jun; Lu, Wei; Tong, Yuxin; Yang, Qichang (Frontiers in Plant Science, 2016)
Red and blue light are both vital factors for plant growth and development. We examined how different ratios of red light to blue light (R/B) provided by light-emitting diodes affected photosynthetic performance by investigating parameters related to photosynthesis, including leaf morphology, photosynthetic rate, chlorophyll fluorescence, stomatal development, light response curve, and nitrogen content. In this study, lettuce plants (Lactuca sativa L.) were exposed to 200 μmol•m-2•s-1 irradiance for a 16 h•d-1 photoperiod under the following six treatments: monochromatic red light (R), monochromatic blue light (B) and the mixture of R and B with different R/B ratios of 12, 8, 4, and 1. Leaf photosynthetic capacity (Amax) and photosynthetic rate (Pn) increased with decreasing R/B ratio until 1, associated with increased stomatal conductance, along with significant increase in stomatal density and slight decrease in stomatal size. Pn and Amax under B treatment had 7.6% and 11.8% reduction in comparison with those under R/B=1 treatment, respectively. The effective quantum yield of PSII and the efficiency of excitation captured by open PSII center were also significantly lower under B treatment than those under the other treatments. Shoot dry weight increased with increasing R/B ratio with the greatest value under R/B=12 treatment. The increase of shoot dry weight was mainly caused by increasing leaf area and leaf number, but no significant difference was observed between R and R/B=12 treatments. Based on the above results, we conclude that quantitative B could promote photosynthetic performance or growth by stimulating morphological and physiological responses, yet there was no positive correlation between Pn and shoot dry weight accumulation.